In vitro evaluation of selective mahua flowers endophytes as a bioinoculant on Greengram [Vigna radiata (L.)] - POOJA PATEL; RAMAR KRISHNAMURTHY; ASHOK SHAH (International Journal of Pharma and Bio Sciences, 2017)
The importance of plant growth promoting microbes in plant growth promotion has been documented. However, reports of effective endophytes from the mahua flowers are limited. In this study, total seven bacteria and two yeast endophytes were isolated. One bacterial isolate (MSB1) and two yeast isolates (MSY1 & MSY2) were found to be most persistent and dominant among all on cultured media. MSB1, MSY1 and MSY2 isolates were further studied for their multiple plant growth promoting traits viz; indole acetic acid, siderophore production, phosphorous solubilization and nitrogen fixation. Isolates MSB1, MSY1 and MSY2 were able to produce 18.57, 15.14 and 39.64 μg/ml of indole acetic acid, respectively. Phosphate solubilising activity was found in both yeast; MSY1 (12.24 μg/ml) and MSY2 (10.79 μg/ml). Bacteria (MSB1) produced 47.80% of siderophore unit. Based on microbiological and molecular characteristics, microbes showing PGP traits were identified as Bacillus amyloliquefaciens (MSB1), Rhodotorula sp. (MSY1) and Pichia kudriavzevii (MSY2). In vitro study using greengram as an indicator crop revealed that inoculation of individual strain increased shoot length, root length and vigour index of greengram seedling. This study suggests that these isolates have potential to be used as bioinoculants for greengram production.